(untitled) (Південний архів (історичні науки), 2025)
Aim of the article – to analyse the formation of state policies on the bone recycling in early Soviet Ukraine, focusing on the needs of Soviet industry, collection spaces, methods and challenges, key actors, and the relationships between them during this activity.Novelty of the study lies in the absence of a dedicated, in-depth analysis of bones as a resource, which this article seeks to address.Methodology: the study is based on documents from Ukrainian archives previously unused in scholarship, materials from Soviet press and popular science literature of the period, and statistical collections. Conclusions: It is concluded that the case of bone collection is indicative of the early Soviet resource management system and serves as a small-scale model of the organization of waste recycling in the 1920s–early 1930s. It is shown that during this period the USSR began developing a model of resource extraction from the periphery, as waste was considered a valuable resource equivalent to grain, forests, coal, gas, and water. Continuity with Russian Imperial collection practices is identified, alongside a demonstrated link between industrialization, urbanization, and the emergence of new collection spaces and methods in the Ukrainian SSR. It is demonstrated that even during the NEP period, the administrative model of recycling illustrates the authorities’ efforts to control resource flows through a planned economy and hierarchical management, involving both state and private collectors. At the same time, incompatible approaches, imbalances between collection costs and procurement prices, and low motivation among workers and the population led to systemic problems, plan failures, and intense competition among collectors, who functioned simultaneously as partners and competitors. It is concluded that while the economic efficiency of early Soviet bone recycling remains questionable, the practice clearly served important political functions: it subordinated the republic’s economy to central directives, demonstrated the mobilization potential of peripheral resources, and showcased the Soviet system’s capacity to effectively organize and utilize them.